Critical vitrification steps towards survival of Garcinia hombroniana (Clusiaceae) shoot tips after cryopreservation - Sulong, Norafarain (2018)
A cryopreservation protocol was developed for in vitro shoot tips of Garcinia hombroniana using the vitrification technique. Four critical steps in the technique were investigated, namely preculture, loading, dehydration with Plant Vitrification Solution 2 (PVS2), and unloading. Shoot tips precultured for 48 hr gave significantly higher survival (75 %) compared to 24 hr preculture (50 %) after cryopreservation. Treatment with 1 M glycerol plus 0.4 M sucrose as a loading solution gave higher survival (45.83 %) compared to the other treatments (0.4 M sucrose + 2 M glycerol; 0.4 M sucrose). Shoot tips dehydrated with PVS2 for 25 min gave the highest survival after immersion in liquid nitrogen. Stepwise PVS2 treatment for 15 min with 50 % PVS2 followed by 10 min with 100 % PVS2 solution improved survival of the shoot tips after cryopreservation (41.67 %). Murashige and Skoog medium with 0.4 M sucrose gave significantly higher survival (66.67 %) than MS with 1.2 M sucrose (25 %) as an unloading solution. Water content was shown to decrease throughout the whole vitrification steps from 6.83 ± 1.66 g g-1 dw for fresh shoot tips down to 2.93 ± 0.28 g g-1 dw after PVS2 treatment. Further study on each step including recovery medium is required to improve the survival. Nevertheless, the present study showed the potential of using the vitrification technique for cryopreservation of G. hombroniana.